Penyuluhan Pemanfaatan Teknologi Pangan Dalam Meningkatkan Daya Saing Dan Produksi UMKM Di Kelurahan Klampis Ngasem - Fachmi Nursyamsi; Prima Nasrul Aziz; Sabrina Ayu Afira; Roziana Febrianita (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
Micro, small and medium enterprises or MSMEs play an important role in improving the economy of a region and the country's economy. However, in the production cycle, processed food requires prerequisites that must be considered because its quality is easily damaged. One of the factors that often results in defects in MSMEs processed food products is the lack of concern for food safety. The method used in this service activity is counseling. The result of this counseling is that MSMEs actors in Klampis Ngasem Village, Surabaya City know the use of food added ingredients and hazardous materials in food. The purpose of this service activity is to educate MSMEs in Klampis Ngasem Village, Surabaya City about the importance of using food preservation and packaging technology extend the shelf life of the product while still complying with food safety regulations. so that MSMEs actors can make food products that are safe, competitive, of good quality, and have high selling value.